Cultural competency and communication skills of dental students: clinical supervisors' perceptions. (15th July 2016) - Mariño, R.; Ghanim, A.; Morgan, M.; Barrow, S.
Abstract: Objectives: This study explored clinical supervisor's (CS) views and experiences of dental students' cultural competence (CC) at the Melbourne Dental School, The University of Melbourne, Australia. Additionally, this study explored CS insights into how CC could be taught. Methods: Semi‐structured one‐to‐one interviews were organised with consenting CS. Interview topics included the following: the importance of CC, communication and rapport, the role of culture in oral health and the need for curriculum enhancement. Interviews were recorded, transcribed and thematically analysed to identify key areas using NVivo software. Results: A total of 12 CS participated in this study. CS acknowledged the importance of CC and felt that it was important for good patient management. CS's definition of CC focused primarily on language and communication skills. CS felt that dental students were generally able to manage culturally diverse patients. However, CS indicated that additional training in this area would be beneficial. Concerns were raised about the students' ability to establish good rapport and communication, with CS highlighting areas such as misuse of interpreters and use of jargon. CS felt that clinical experience, confidence and a positive attitude are effective tools for overcoming cultural barriers. Furthermore, some CS also felt that cultural competency was a skill that is learnt through experience. Conclusions: For most CS, cultural competence was an important part of the clinician–patient exchange which would benefit from enhanced curriculum. They also highlighted areas where transcultural education could be improved. The majority of CS believed dental students managed culturally diverse patients well.